2009
DOI: 10.1016/j.drugalcdep.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and opioid dependence medications: Prescription trends, overall and by physician specialty

Abstract: Over the past decade, advances in addiction neurobiology have led to the approval of new medications to treat alcohol and opioid dependence. This study examined data from the IMS National Prescription Audit (NPA) Plus™ database of retail pharmacy transactions to evaluate trends in U.S. retail sales and prescriptions of FDA-approved medications to treat substance use disorders. Data reveal that prescriptions for alcoholism medications grew from 393,000 in 2003 ($30 million in sales) to an estimated 720,000 ($78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
167
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 14 publications
7
167
0
1
Order By: Relevance
“…An estimate from retail sales data now 10 years old suggested that, at most, approximately 9% of the population needing alcoholism treatment received the equivalent of a single prescription in 1 year (Mark et al, 2009), and many of these prescriptions were written by psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…An estimate from retail sales data now 10 years old suggested that, at most, approximately 9% of the population needing alcoholism treatment received the equivalent of a single prescription in 1 year (Mark et al, 2009), and many of these prescriptions were written by psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, it was approved by the FDA for the maintenance of abstinence from alcohol in detoxified alcohol-dependent patients. A recent survey found that acamprosate is now the most widely prescribed medication for the treatment of alcoholism in the United States of America (Mark et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, DSF itself is a very inexpensive drug. Its current FDA-approved form for treating alcoholism, manufactured under the trade name Antabuse®, is an oral tablet and costs on average only $78 per prescription as of 2007 [30]. In contrast, many cancer drugs can cost thousands of dollars per year-for example, goserelin acetate, an FDAapproved drug for the treatment of breast and prostate cancer can cost over $5,000 for two years [31].…”
mentioning
confidence: 99%